KARAKTERISTIK, KEMAMPUAN BERBAHASA INGGRIS DAN PENGGUNAAN MEDIA PELAKU USAHA MIKRO KECIL MENENGAH (UMKM) DESA WISATA - Riyantini, Rini; Suprasti, Devi (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Sustainable tourism development which is the government's priority at this time is not enough to infrastructure support, but in accordance with the objectives of community welfare based on human resource capacity, local wisdom and ecosystem maintenance can be realized if it is balanced by mapping the potential and capacity of the community. In accordance with its target, tourism has become a source of foreign exchange for the country by visiting foreign tourists as well as a place to promote Indonesian products, culture and natural resources abroad. For this reason, good communication from Indonesian people is needed for tourists, so that they can attract other tourists on an ongoing basis. One of them is with good English skills and the use of information technology as a medium of communication between Indonesian people and tourists. This study illustrates how the ability of English and the use of media among the community, especially SMES actors who are the pillars of the national economy as well. The results showed that between English language skills and media use were positively related, meaning that the higher the English language skills of the people the higher the level of media use..